Best Answer

-9h - 6 + 12h + 40 = 22, simplifying this gives

12h - 9h + 40 - 6 = 22

3h + 34 = 22, taking 34 off both sides gives

3h + 34 - 34 = 22 - 34

3h = -12, thus

h = -12/3 = -4

Q: Solve this equation-9h-6 plus 12h plus 40 equals 22?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-9h-6+12h+40=22 -9h+12h=22-40+6 3h=-12 h=-4

It is: 12h+5h = 17h

8059

20/16 = h/12;Cross multiply: 16 x h = 20 x 12h = 20 x 12/16 = 240/16 = 15 in

You can plug those values in the pythagorean theorem and find the hypotenuse: h = ((h - 3)2 + (h - 6)2)1/2 ∴ h2 = h2 - 6h + 9 + h2 - 12h + 36 ∴ h2 = 2h2 - 18h + 45 ∴ h2 - 18h + 45 = 0 ∴ (h - 3)(h - 15) = 0 ∴ h = 3, 15 So the length of the hypotenuse will be either 3 or 15. It can't be 3 though, since that would make the other sides 0 and -3, which is impossible. The answer then is 15. The triangle has a hypotenuse of 15, and sides of 12 and 9

Related questions

h= -4

-9h-6+12h+40=22 -9h+12h=22-40+6 3h=-12 h=-4

-9h-6+12h+40=22

-9-6+12h+40=22

-9h - 6 + 12h + 40 = 22 ie 3h = 22 + 6 - 40 h= -12/3 = -4

h-9h-6+12h+40 = 22 h-9h+12h = 22+6-40 4h = -12 h = -3

The solution to this equation is that h is equal to -4. You can substitute this value for h into the equation to get -4 x -9 - 6 plus 12 x -4 plus 40 equals 22, or 36 - 6 plus - 48 plus 40 equals 22.

-9h-6+12h+40 = 22 3h+34 = 22 3h = 22-34 3h = -12 h = -4

It is: 12h+5h = 17h

19h which = 7PM in the evening

If you're trying to find h... -9h - 6 + 12h + 40 = 22 3h = -12 h = -4 If you're not trying to find h... You're question makes no sense. When asking a question, try to define something for a person to answer.

12h-17-h+16-2h =12h-3h-17+16 =9h-1,if you mean the value of h,then h =1/9